Implementasi Fungsi Perencanaan dalam Membangun Perpustakaan Digital Berbasis Website di Perpustakaan BPK Penabur Cirebon - Liyana, Andhiny Haarisah; Rachmawati, Tine Silvana; Lusiana, Elnovani (Universitas Sebelas Maret Library, 2022)
This study aims to determine the implementation of the planning function to build a website-based digital library. The research method uses descriptive qualitative. The theory used is one of the functions of digital library management, the planning function. Data collection techniques are carried out through interviews, observations, documentation, and literature studies, then the data is described, explained, or interpreted in the results and discussion. The results of the study reveal that planning to build a website-based digital library starts with stating the objectives that are packaged in the vision and mission of the BPK Penabur Cirebon digital library website. Hardware and software planning is provided and developed both independently and in collaboration with third parties. Planning for the uploading process on the BPK Penabur Cirebon digital library website is to provide e-books that come from a credible and trusted download platform and are legal to use. Development and maintenance planning is carried out by planning innovations that will be applied to digital library websites that aim to provide user satisfaction. Maintenance is a plan to check the hardware and software that support the digital library website. The budget is channeled for the purposes of the digital library website, which consists of the purchase or rental of hardware and software. Planning for HR is carried out by training or briefing on digital library operations and writing information and news to be published in websites digital library.